Hungary Country report on digitalization and international comparison within the frameworks of the CA21107 COST Action Work inequalities in later life redefined by digitalization (DIGI-net) - Mónika, Modla; Ildikó, Modláné Görgényi; Andrea, Ferenczi (Magyar Gerontológia, 2023)
The Association For Women’s Career Development In Hungary (AWCDH) participates in the CA21107 COST Action “Work inequalities in later life redefined by digitalization (DIGI-net)”. AWCDH members participate in research activities in all 5 Working Groups.